A Guide for Developing ELT Materials by Using the Linguistic Landscape of the Salamis Road - Kılgın, Sevgi; Erozan, Fatos (My University, 2025)
There has been a burgeoning interest in the pedagogical potential of linguistic landscape (LL) research for language education. Using LL-based pedagogical activities not only exposes students to authentic target language input but also creates opportunities for genuine language practice. This study has three main goals: to explore the LL of the Salamis Road vicinity in Famagusta, North Cyprus; to find out how English is used on the LL signs, and to develop ELT materials employing the collected LL data. The analysis of 418 top-down and bottom-up LL signs revealed that the LL of the vicinity is largely composed of bottom-up signs, and Turkish is the predominant language although English language is also widely used. The LL signs including English language were then used to design ELT materials for developing students’ speaking and writing skills. The present study can be regarded as a guide for developing LL-based materials for ELT.
Keywords: ELT; materials development; linguistic landscape; LL signs